Influence of Different Acid Treatments on the Radiocarbon Content Spectrum of Sedimentary Organic Matter Determined by RPO/Accelerator Mass SpectrometryABSTRACT - Bao, Rui; McNichol, Ann P; Hemingway, Jordon D; Lardie Gaylord, Mary C; Eglinton, Timothy I (Radiocarbon, 2019)
In practice, obtaining radiocarbon (C-14) composition of organic matter (OM) in sediments requires first removing inorganic carbon (IC) by acid-treatment. Two common treatments are acid rinsing and fumigation. Resulting C-14 content obtained by different methods can differ, but underlying causes of these differences remain elusive. To assess the influence of different acid-treatments on C-14 content of sedimentary OM, we examine the variability in C-14 content for a range of marine and river sediments. By comparing results for unacidified and acidified sediments [HCl rinsing (Rinse(HCl)) and HCl fumigation (Fume(HCl))], we demonstrate that the two acid-treatments can affect C-14 content differentially. Our findings suggest that, for low-carbonate samples, Rinse(HCl) affects the Fm values due to loss of young labile organic carbon (OC). Fume(HCl) makes the Fm values for labile OC decrease, leaving the residual OC older. High-carbonate samples can lose relatively old organic components during Rinse(HCl), causing the Fm values of remaining OC to increase. Fume(HCl) can remove thermally labile, usually young, OC and reduce the Fm values. We suggest three factors should be taken into account when using acid to remove carbonate from sediments: IC abundance, proportions of labile and refractory OC, and environmental matrix.

Dimensions of Radiocarbon Variability within Sedimentary Organic MatterABSTRACT - Bao, Rui; McNichol, Ann P; McIntyre, Cameron P; Xu, Li; Eglinton, Timothy I (Radiocarbon, 2018)
Organic carbon (OC) radiocarbon (14C) signatures in marine surface sediments are highly variable and the causes of this heterogeneity remain ambiguous. Here, we present results from a detailed 14C-based investigation of an Arabian Sea sediment, including measurements on organic matter (OM) in bulk sediment, specific grain size fractions, and OC decomposition products from ramped-pyrolysis-oxidation (RPO). Our results show that 14C ages of OM increase with increasing grain size, suggesting that grain size is an important factor controlling the 14C heterogeneity in marine sediments. Analysis of RPO decomposition products from different grain size fractions reveals an overall increase in age of corresponding thermal fractions from finer to coarser fractions. We suggest that hydrodynamic properties of sediment grains exert the important control on the 14C age distribution of OM among grain size fractions. We propose a conceptual model to account for this dimensionality in 14C variability that invokes two predominant modes of OM preservation within different grain size fractions of Arabian Sea sediment: finer (<63 μm) fractions are influenced by OM-mineral grain aggregation processes, giving rise to relatively uniform 14C ages, whereas OM preserved in coarser (>63 μm) fractions includes materials encapsulated within microfossils and/or entrained fossil (14C-depleted) OC hosted in detrital mineral grains. Our findings highlight the value of RPO for assessment of 14C age variability in sedimentary OC, and for assessing mechanisms of OM preservation in aquatic sediments.
Keywords: arabian sea; grain size; hydrodynamic processes; organicmatter; radiocarbon; ramped pyrolysis-oxidation